Education Decentralization Policy in Improving the Quality of Education - Ritman Hendra; Fadriati Fadriati; Yudi Nur Supriadi; Handriadi Handriadi; Suhendri Suhendri (Edumaspul: Jurnal Pendidikan, 2023)
This study discusses the decentralization of Education, which at first was fully controlled by the central Government. With the decentralization of Education, local governments have the authority to regulate and control Education in their regions in an effort to improve the quality of Education. It has been 23 years since this Regional Autonomy has been present in the country with various packages carried out by the Government for Education in particular. That long time will actually make Indonesian education quality, both in terms of input, process and results. However, it creates new problems in the regions, for example: the existence of regional heads numbering two / three / so on Education, so that the meaning of Autonomy in the field of Education is not evenly distributed in the regions they lead. Whereas the mandate of the 1945 Constitution is clear, that Education is a right for all Indonesian people whose aim is to educate the nation's life, another meaning is that Education will make a person qualified, both religiously, morally and socially. This study uses a qualitative approach with the type of literature study. Data collected from various journal articles and books that are in accordance with the research topic through content analysis. This type of research is a qualitative research. The results of this study show that the decentralization of Education is actually fully implemented by the local Government, so that the impact can be felt by the school community in an effort to improve the quality of Education.